Impact of the Quadrivalent HPV Vaccine on Disease Recurrence in Men Exposed to HPV Infection: A Randomized Study. (1st November 2014) - Coskuner, Enis Rauf; Ozkan, Tayyar Alp; Karakose, Ayhan; Dillioglugil, Ozdal; Cevik, Ibrahim
Abstract: Introduction: Human papillomavirus (HPV) is one of the most common sexually transmitted infections and is the cause of several different diseases in men and women. Although little is known about HPV infection in men, they are also in the risk group of HPV infection and play an important role in transmitting the virus to women. Aim: To define the efficacy of the HPV vaccine through cross-immunization and its role in clearance of HPV infection, and to assess infection-associated factors in men. Methods: This prospective randomized clinical study enrolled 171 evaluable men with genital warts between June 2009 and October 2013. After the initial treatment intervention, 91 patients were randomly assigned to receive HPV vaccine in three doses. Eighty patients were in the control (unvaccinated) group. One hundred-eleven men were single and 60 men were married. Patients who had previous treatment for pre-existing warts and medical disorders that needed chronic treatment or immunosuppression were not included in the randomization. Also 29 men with follow-up less than 12 months and incomplete vaccination were not included. Main Outcome Measures: The patients were assessed regarding age, condom use, marital status, number of visible genital warts, and smoking status. Post-treatment follow-up was monthly up to 12th month. Results: Mean age was 34±7.6. One hundred fifteen patients were smokers. For the recurrence of warts, age, smoking, vaccination status were insignificant and marital status was significant in the univariable analysis; only marital status preserved significance (HR: 2.0 CI:1.29–3.12 P =0.002) in the multivariable analysis including vaccination status, marital status, and smoking. Conclusion: Among the investigated factors vaccination status was not but marital status significantly influenced wart recurrence. Married men had more recurrences in our population. Larger multicenter randomized clinical trials are lacking and seriously required to investigate the therapeutic effect of current quadrivalent HPV vaccine in genital warts.